Identification of Lipases Involved in PBAN Stimulated Pheromone Production in Bombyx mori Using the DGE and RNAi Approaches - Du, Mengfang; Yin, Xinming; Zhang, Songdou; Zhu, Bin; Song, Qisheng; An, Shiheng (PLOS ONE, 2012)
Background Pheromone biosynthesis activating neuropeptide (PBAN) is a neurohormone that regulates sex pheromone synthesis in female moths. Bombyx mori is a model organism that has been used to explore the signal transduction pattern of PBAN, which is mediated by a G-protein coupled receptor (GPCR). Although significant progress has been made in elucidating PBAN-regulated lipolysis that releases the precursor of the sex pheromone, little is known about the molecular components involved in this step. To better elucidate the molecular mechanisms of PBAN-stimulated lipolysis of cytoplasmic lipid droplets (LDs), the associated lipase genes involved in PBAN- regulated sex pheromone biosynthesis were identified using digital gene expression (DGE) and subsequent RNA interference (RNAi). Results Three DGE libraries were constructed from pheromone glands (PGs) at different developed stages, namely, 72 hours before eclosion (−72 h), new emergence (0 h) and 72 h after eclosion (72 h), to investigate the gene expression profiles during PG development. The DGE evaluated over 5.6 million clean tags in each PG sample and revealed numerous genes that were differentially expressed at these stages. Most importantly, seven lipases were found to be richly expressed during the key stage of sex pheromone synthesis and release (new emergence). RNAi-mediated knockdown confirmed for the first time that four of these seven lipases play important roles in sex pheromone synthesis. Conclusion This study has identified four lipases directly involved in PBAN-stimulated sex pheromone biosynthesis, which improve our understanding of the lipases involved in releasing bombykol precursors from triacylglycerols (TAGs) within the cytoplasmic LDs.